1996
DOI: 10.1007/bf01271260
|View full text |Cite
|
Sign up to set email alerts
|

CSF inositol does not predict antidepressant response to inositol

Abstract: CSF inositol was reported to be reduced in depression and inositol has been reported to be effective in treatment of depression. We studied CSF inositol in 18 drug-free depressed patients and 36 normal controls; the depressed patients then participated in an open trial of 18 gm daily inositol treatment for 4 weeks. There was no difference in pre-treatment CSF inositol between depressed patients and controls. CSF inositol levels did not predict response on the Hamilton Depression Scale to 4 weeks of inositol tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 12 publications
(6 reference statements)
0
8
0
Order By: Relevance
“…The present study was a satellite part of a previous study [33] approved by the local Helsinki committee and the ministry of health. It included two groups.…”
Section: Methodsmentioning
confidence: 99%
“…The present study was a satellite part of a previous study [33] approved by the local Helsinki committee and the ministry of health. It included two groups.…”
Section: Methodsmentioning
confidence: 99%
“…The study was an add-on to another research project approved by the review board and ethics committee [25]. Thirteen patients participated in the study, 2 males, 11 females, mean age 56 (range 29-70).…”
Section: Methodsmentioning
confidence: 99%
“…Barkai et al (2) reported that inositol is reduced in cerebrospinal fluid in patients with bipolar and unipolar depression, although others could not replicate this finding (3). In a double-blind, controlled study (4), Levine et al administered 12 g/day of inositol or placebo to 28 depressed patients for 4 weeks.…”
mentioning
confidence: 99%